Effect of nutrients starvation in the cell cycle synchronization of cell suspension cultures of Jatropha curcas L. (2018)
ABSTRACT:The knowledge about the processes that control cell cycle activity in J. curcas has not yet been addressed. Cell suspension cultures offer an attractive alternative to carry out this kind of studies in a simplified biological system. Nevertheless, the cell suspensions exhibit a high degree of heterogeneity concerning cell cycle distribution; therefore, synchronization methods must be previously established for this plant species. In the present research, cell suspensions of J. curcas were used to assess phosphorus, nitrogen or sucrose starvation as cell cycle synchronization approaches. Cell suspension cultures were established from the endosperm of seeds using a method for the enzymatic breakdown, without a previous callogenesis stage. The cell suspensions reached a maximum growth rate of 0.15 d−1 and a doubling time of 4.8 d. Microscopy analyses showed amyloplasts in some of the cells; however, oil and protein bodies were not observed. Regarding cell cycle synchronization, the results indicated that phosphorus or nitrogen starvation did not affect the cell-cycle arrest in the G0/G1 phase. However, the sucrose depletion for three days induced an accumulation of 67% of the cells in the G0/G1 phase. This effect was reversed with the addition of a carbon source. Moreover, these culture conditions generated a population of cells (approx. 5%) with a higher DNA content (3n > 6n), which was interpreted as the activation of an endoreplication process. Our findings suggest that nutrient starvation can affect in a differential way the cell synchronization process.